Molecular cloning and functional expression of delta 9-fatty acid desaturase from Antarctic Pseudomonas sp. A3 and Pseudomonas sp. A8 - Garba, Lawal (2017)
Fatty acid desaturase enzymes are capable of inserting double bonds between carbon atoms of saturated fatty acyl chains to produce unsaturated fatty acids. The enzymes are used by the Antarctic microorganisms to increase the amount of cellular unsaturated fatty acids, which maintain the proper membrane fluidity at low temperatures. The Δ9-fatty acid desaturase enzyme catalyses introduction of the first double bond between C9 and C10 positions of saturated fatty acyl chains, a critical step in the biosynthesis of many polyunsaturated fatty acids. Although many Δ9-fatty acid desaturases were studied from animals, plants and bacteria, to date the number of the Δ9-fatty acid desaturase enzymes reported from Antarctic bacteria is very limited.The main objectives of this research were to clone and functionally express Δ9-fatty acid desaturases. Five isolates of Antarctic bacteria were screened for their ability to produce unsaturated fatty acids at low temperatures and identified as Pseudomonas sp. A3, Pseudomonas sp. A8, Arthrobacter sp. 1B, Arthrobacter sp. 3B and Arthrobacter sp. PB based on 16S rDNA identification supported by morphological characteristics and biochemical tests. The bacteria were positive palmitoleic and oleic acids producers except Arthrobacter sp. 1B. Presence of a double bond at C9 positions of these fatty acids suggested that the isolates would be potential Δ9-fatty acid desaturase producers. Total unsaturation was observed to be higher in Arthrobacter sp. 3B (47.24%), followed by Pseudomonas sp. A8 (45.09%), Pseudomonas sp. A3 (33.17%), and Arthrobacter sp. PB (31.92%). Although Arthrobacter sp. 3B had the highest unsaturation, isolation of Δ9-fatty acid desaturase gene from this bacterium was unsuccessful. Hence, Pseudomonas sp. A3 and Pseudomonas sp. A8 were selected for Δ9-fatty acid desaturase gene isolation. The genes were successfully PCR amplified from Pseudomonas sp. A3 and Pseudomonas sp. A8, cloned and heterologously expressed in Escherichia coli Transetta (DE3) under the control of T7 promoter. The genes isolated from Pseudomonas sp. A3 and Pseudomonas sp. A8 were designated as PA3FAD9 and PA8FAD9, respectively each having an open reading frame of 1,185 bp coding for 394 amino acids with a predicted molecular weight of 45 kDa. Three dimensional structures of both the Δ9-fatty acid desaturases were predicted using YASARA software with suitable templates and used to perform molecular docking of palmitic acid, which predicted the ability of the enzymes to use palmitic acid as a substrate during the in vivo studies. Functional expression of each gene was confirmed by GCMS, which showed functionally expressed Δ9-fatty acid desaturases capable of increasing the overall cellular palmitoleic acid content of the recombinant E. coli cells that carried PA3FAD9 and PA8FAD9 genes leading to two-fold increase upon expression at 15 and 20 oC, respectively. Exogenous stearic acid was incorporated into the E. coli phospholipids before it was desaturated by the Δ9-fatty acid desaturases to produce oleic acids when added into the E. coli growth medium. The results confirmed novel Δ9-fatty acid desaturases that could be used to enhance unsaturated fatty acid production in suitable hosts. In conclusion, the two Δ9- fatty acid desaturase proteins were functionally expressed and increased the overall cellular unsaturated fatty acid contents of the recombinant E. coli. The enzymes could be used in polyunsaturated fatty acids production through co-expression with other genes of desaturases and elongases in a host that can produce unsaturated fatty acids using the recombinant DNA technology.